Interior lodgepole pine (Pinus contorta var. latifolia) and white spruce (Picea glauca) orchard capacity and demand in Alberta, Canada - Kennedy L. Mitchell; Barb. R. Thomas (The Forestry Chronicle)
Seed orchards that produce genetically selected or improved seeds for forest adaptation and productivity are a fundamental element of successful tree improvement programs. A productive orchard maximizes the benefits of tree improvement initiatives by meeting regional seed demands for annual artificial regeneration. To understand the current capacity, of six interior lodgepole pine (Pinus contorta var. latifolia) and eight white spruce (Picea glauca) orchards in Alberta to produce improved seed and meet reforestation needs, we reviewed the historical annual seed supply and demand. Based on reported annual seed production, we estimated the theoretical productive orchard area required to meet future seed demand. From this work, a tool was developed to visually represent the estimated orchard area required to meet seed production targets for each tree improvement program based on user-defined variables. We identified several under producing orchards, primarily for interior lodgepole pine. In the programs studied, additional productive orchard area will be required to meet seed demand targets and maximize the benefits of the tree improvement programs they serve.